2000
DOI: 10.1021/jf990358i
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Docosahexaenoic Acid Can Alter the Surface Expression of CD4 and CD8 on T Cells in Peripheral Blood

Abstract: The effect of dietary docosahexaenoic acid (DHA) on T cell states in peripheral blood was investigated. Weanling male C57Bl/6N mice were kept on one of three 10% fat diets containing various amounts of DHA and linoleic acid for 4 weeks. Changing the concentration of dietary DHA did not alter the proportion of T cells expressing CD4 or CD8. However, increasing the concentration of dietary DHA lowered the expression of CD4 and CD8 on the cell surface. The decreased expression of these surface molecules involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…As a consequence, a detrimental effect may occur, because host defense against bacterial and other antigens could be compromised (33). Likewise, a significant reduction of the expression of CD4 or CD8 on cell surfaces has recently been documented after dietary supplementation with DHA (34). The present results have confirmed that some dietary lipids are related to a reduction of lymphocyte proliferation stimulated by ConA or LPS.…”
Section: Discussionsupporting
confidence: 78%
“…As a consequence, a detrimental effect may occur, because host defense against bacterial and other antigens could be compromised (33). Likewise, a significant reduction of the expression of CD4 or CD8 on cell surfaces has recently been documented after dietary supplementation with DHA (34). The present results have confirmed that some dietary lipids are related to a reduction of lymphocyte proliferation stimulated by ConA or LPS.…”
Section: Discussionsupporting
confidence: 78%
“…The number of lymphocytes CD4 + and CD8 + cells, and spleen mononuclear CD4 + , CD8 + and IgM + cells did not differ between treatment groups (Table 5). Similar results of no difference between layer birds fed n-3 and n-6 fatty acids have been reported (Sasaki et al 2000;Wang et al 2000). Kelley et al (1991) reported no change in human peripheral cells by feeding n-3 fatty acids.…”
Section: Immune Cells Phenotypingsupporting
confidence: 80%
“…The changes brought about in the immune response of layer birds fed CLA, SFA, n-6 and n-3 fatty acids cannot be explained based on CD4 + /CD8 + cell population. Different fatty acids impede intracellular interaction involved in antigen recognition by T cells and antigen presenting cells and influence cell-mediated and antibody-mediated response differently (Sasaki et al 2000). One other possibility is that the difference in the level of activation of CD4 + /CD8 + positive cells, without affecting their absolute numbers, could have caused this effect.…”
Section: Immune Cells Phenotypingmentioning
confidence: 99%
“…The percentages of T‐lymphocyte subpopulations in the spleen were measured by flow cytometry analysis 11. Splenocyte suspensions (1 × 10 6 cells mL −1 ) were doubly labelled with fluorescein isothiocyanate (FITC)‐conjugated and phycoerythrin (PE)‐conjugated antibodies for 15 min at room temperature (18–25 °C).…”
Section: Methodsmentioning
confidence: 99%